Playing traditional games vs. free-play during physical education lesson to improve physical activity: a comparison study - 'Arif B. Azlan; Nadzirah Ismail; Nor Farah Mohamad Fauzi; Ruzita Abd. Talib (IP Iermakov S.S., 2021)
Background and Study Aim. Non-sport activities like traditional games can be a practical way to promote physical activity (PA) during physical education (PE) lessons, especially among those who are less inclined towards sports. The purpose of this study is to compare the PA variables and acceptance between playing traditional games and free-play during physical education lessons among secondary school students. Material and Methods. Fifty-six (n = 56) subjects participated in this study wore accelerometers for a total of 40 minutes during each PE lesson to record PA. In the first week, a 40-min free-play PE lesson was done while in the second week, a 40-min PE lesson incorporated with traditional games (TG-PE lesson) was done. After following both lessons, subjects filled up a questionnaire on acceptance of TG-PE and free-play PE lessons. Results. The mean total activity count (p < 0.05) and time spent in moderate-to-vigorous physical activity (MVPA) (p < 0.05) were 20% and 19% greater respectively during TG-PE lesson compared to free-play PE lesson. The mean acceptance scores showed students preferred playing TG (19.29 ± 4.21; p < 0.00) over free-play PE lesson (17.59 ± 3.13). Conclusions. In conclusion, incorporating fun and meaningful activities such as TG during PE lessons can serve as an alternative strategy to promote PA during school hours. Further studies are warranted to determine other types of TG that may promote PA among secondary school students.